Re-imagining teacher mentoring for the future - Larsen, Ellen; Jensen-Clayton, Cecily; Curtis, Elizabeth; Loughland, Tony; Nguyen, Hoa T. M. (Professional development in education, 2025)
Teachers are dealing with a profession characterised by rapidly evolving educational research, societal shifts, and political agendas. They are faced with unforeseen events that create educational futures that are yet unknown, with the global pandemic a clear example. Mentoring has a long history as an approach to support teachers, particularly those in the early stages of their careers, to navigate the challenges of the profession and build professional capacity. The unprecedented complexity of the current educational landscape demands now, more than ever, that mentoring for early career teachers (ECTs) extends beyond standards-driven capacity building to nurture future-focused dispositions. This paper conceptualises the Future-focused Mentoring model (FfM) for the current educational context, framed by the intellectual virtues for the transformation of self, relationships, and teacher practice that leverages and celebrates intellectual imagination, courage, open-mindedness, and tenacity. In proposing this model, we draw on a strong theoretical and empirical base to articulate the principles of a mentoring model that is relational, mindful and future-focused. This model has been conceptualised as a way forward to support and sustain ECTs' effectiveness for the future and longevity in the profession.